An Error with Consequences: Marcellus of Side, a personal physician of the Emperor Hadrianus? - Johannes Nollé (Gephyra, 2015)
In the first volume of the new journal ‹Philia› Mustafa Adak and two of his assistants publish some inedited inscriptions of Side in Pamphylia. Many of the transcriptions and commentaries leave much to be desired, but in this paper Johannes Nollé concentrates only on the extremely defective edition of an important honorary inscription devoted to the Sidetan doctor and poet Markellos, who lived in the times of the emperor Hadrianus. Nollé criticizes the transcription and the grammatical understanding as well as the interpretation of this interesting text consisting of only five words: Mάρκελλον | Σίδητον | ἀρχιιατρὸν | ἡ πατρίς. Σίδητον is not an apposition to Μάρκελλον in the accusative, as Adak and his assistants want to make us believe, but a genitive attribute to ἀρχιιατρόν. As the ethnikon is in fact Σιδήτης and a variant Σίδητος – which Adak and his assistants implicitly suggest – is unattested, we have to interpret ΣΙΔΗΤΟΝ as Σιδητ῱ν (= Σιδητῶν). Consequently, in this new inscription Markellos is praised as Side’s city doctor. That is why we have no reason to assume, as Adak and his assistants did, that this inscription shows that Markellos was emperor Hadrianus’s personal doctor. Exactly the opposite is probable: This new inscription as well as already existing evidence make it very likely that Markellos was a famous city doctor of Side whose medical knowledge and poetical abilities made him known far beyond Side. It is not even certain that he was ever in Rome.